The Adolescent Emotional Regulation with a Single Parent and Its Implication on Family Education - Dini Damayanti; Rahmawati Rahmawati; Deasy Yunika Khairun (Jurnal Pendidikan Indonesia Gemilang, 2023)
This study aimed to determine the image of the emotional regulation of adolescents who has a single-parent man. This type of research is qualitative research with a phenomenological study approach. The research place is the subject, who resides in Serang city. The data sources of this study are three teenagers who have single parents caused by death. The results showed that the picture of emotional regulation in adolescents with single parents’ men had not been formed perfectly. Because the subject was still unable to cope with the emotional problems he was experiencing, it wasn't easy to control and express his emotions appropriately. The implications of this study illustrate the importance of a close single-parent man in adolescents to have good emotional skills.